Prevalence of CMV infection among staff in a metropolitan children's hospital - occupational health screening findings - Stranzinger, Johanna; Kindel, Jutta; Henning, Melanie; Wendeler, Dana; Nienhaus, Albert (German Medical Science GMS Publishing House, 2016)
Background: Staff in children's hospitals may run an increased risk of cytomegalovirus (CMV) contact infection leading to a congenital CMV fetopathy during pregnancy. The main risk factor is close contact with inapparent carriers of CMV among infants (<3 years). We therefore examined CMV seroprevalence (SP) and possible risk factors for CMV infection among staff at a children's hospital.Method: In 2014, staff at a metropolitan children's hospital were offered a CMV antibody test in the context of occupational health screening. Besides of anti-CMV immunoglobulin G (anti-CMV IgG) gender, age, profession, number of children and migration background were assessed and used as independent variables in multiple logistic regression. Women without a migration background (MIG) were considered as a separate group.Results: The study included 219 employees. Women showed a significant higher risk than men of being CMV-positive (adjusted odds ratio [aOR] 3.0; 95% CI 1.1-7.8). The risk among age groups of 30 and over was double that of the under-30s (aOR 2.0; 95% CI 1.0-3.9); among those aged 40-plus it was aOR 2.3 (95% CI 1.1-4.7). Staff with an MIG tested more often positive than those without an MIG (95.5% versus 45.7%). CMV SP was 47.7% among women without an MIG. In this subgroup the probability of CMV infection increased with age (p=0.08) as well. Conclusion: In the staff group as a whole there was a significant correlation between CMV SP, country of origin and age. We found no significant differences between occupational groups; perhaps our random sample was too small. Given the low CMV SP particularly in those without MIG, women who want to have children in particular must be protected from CMV infection. Follow-up studies should be undertaken to test whether good workplace hygiene offers sufficient protection for pregnant women and could be an alternative to prohibiting certain activities.